Endocrine pancreatic development: impact of obesity and diet - O'Dowd, Jacqueline F.; Stocker, Claire J. (Frontiers in Physiology, 2013)
During embryonic development, multipotent endodermal cells differentiate to form the pancreas. Islet cell clusters arising from the pancreatic bud form the acini tissue and exocrine ducts whilst pancreatic islets form around the edges of the clusters. The successive steps of islet differentiation are controlled by a complex network of transcription factors and signals that influence cell differentiation, growth and lineage. A Westernised lifestyle has led to an increased consumption of a high saturated fat diet, and an increase in maternal obesity. The developing fetus is highly sensitive to the intrauterine environment, therefore any alteration in maternal nutrition during gestation and lactation which affects the in-utero environment during the key developmental phases of the pancreas may change the factors controlling β-cell development and β-cell mass. Whilst the molecular mechanisms behind the adaptive programming of β-cells are still poorly understood it is established that changes arising from maternal obesity and/or over-nutrition may affect the ability to maintain fetal β-cell mass resulting in an increased risk of type 2 diabetes in adulthood.